2017
DOI: 10.1016/j.jclinane.2016.07.038
|View full text |Cite
|
Sign up to set email alerts
|

Gastric regurgitation in patients undergoing gynecological laparoscopy with a laryngeal mask airway: a prospective observational study

Abstract: Our current results suggest that the use of an LMA in healthy patients undergoing laparoscopic gynecological surgery may be safe. Future studies to confirm or refute our findings are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…However, previous studies have shown that even the use of classical LMA or ProSeal LMA did not increase the risk of passive regurgitation or gastric aspiration 8. The ‘rule of 15’ was defined to avoid regurgitation while using a SAD for laparoscopic surgeries (Trendelenburg tilt <15 degree; peritoneal insufflation <15 cm H 2 O; and duration of abdominal insufflation <15 minutes) 9. All our insufflations were performed in supine position with an abdominal insufflation pressure of 8-10 mm Hg, and all the procedures were completed in reverse Trendelenburg position.…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have shown that even the use of classical LMA or ProSeal LMA did not increase the risk of passive regurgitation or gastric aspiration 8. The ‘rule of 15’ was defined to avoid regurgitation while using a SAD for laparoscopic surgeries (Trendelenburg tilt <15 degree; peritoneal insufflation <15 cm H 2 O; and duration of abdominal insufflation <15 minutes) 9. All our insufflations were performed in supine position with an abdominal insufflation pressure of 8-10 mm Hg, and all the procedures were completed in reverse Trendelenburg position.…”
Section: Discussionmentioning
confidence: 99%
“…(12,17) A major concern of using LMAs in laparoscopic surgery is the risk of regurgitation and aspiration. (24) The incidence of regurgitation varies from 0.2-16.7% in previous reports with different SADs. (25)(26)(27) In this study, gastric re ux was noticed in ve patients (1.72%) in the drainage tube of the device at the end of surgery.…”
Section: Discussionmentioning
confidence: 98%
“…The suprasternal notch test was performed as Eckardt described, [ 19 ] and a lubricated 14F gastric tube was then inserted through the female drainage port. Failed insertion of LMA® Protector™ was defined by any of the following criteria: [ 1 ] failed passage into the pharynx [ 2 ]; malposition (air leaks or end-tidal capnography could not be obtained); and [ 3 ] ineffective ventilation (maximum expired tidal volume < 8 ml/kg, end-tidal carbon dioxide > 45 mmHg, or pulse oxygen saturation < 92% if correctly positioned) [ 13 ]. We allowed a maximum of three attempts with the allocated device.…”
Section: Methodsmentioning
confidence: 99%
“…However, there remain some concerns with the use of LMA in laparoscopic surgery. The major concerns include the potential risk of gastroesophageal regurgitation, aspiration, and difficulties to achieve effective ventilation due to the influence of artificial pneumoperitoneum and postural changes on airway pressure and pulmonary compliance [ 1 , 2 ]. Therefore, many anesthesiologists advocate endotracheal intubation and mechanical ventilation for this kind of procedures despite evidences provided by previous studies.…”
Section: Introductionmentioning
confidence: 99%